Fostering student agency - Maria Hvid Stenalt; Birgitte Lund Nielsen (Dansk Universitetspaedagogisk Tidsskrift)
Student agency is recognised as important to student success. This guide outlines seven strategies for educators in supporting students’ agency construction: (1) Support the students in in becoming students, (2) foster self-determination and autonomy in coursework, (3) be aware of power relations and cultivate an agency-supportive learning environment, (4) give attention to students’ sense of belonging, during studies and in a futures perspective, (5) ensure that the physical and digital environment support students’ opportunities for agentic actions, (6) reframe expressions of resistance as agentic events and (7) examine how to encourage agentic repositions such as students persistence.